Integration of Islamic Values in the Implementation of Academic Supervision at a Muhammadiyah High School in Gowa Regency - Pewangi, Mawardi; Ferdinan; Jarong, Koree (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
This study aims to analyze the application of Islamic values in the implementation of academic supervision at a Muhammadiyah high school in Gowa Regency. The research employs a mixed-methods approach, combining both qualitative and quantitative techniques. The primary objective is to explore the influence of Islamic values on teacher performance. Data collection instruments include a combination of observation sheets and interview guides. Primary data are gathered through observations, interviews, and document analysis, while secondary data comprise relevant documents, books, and other academic sources. The research instruments consist of observation guides, interview protocols, and documentation tools. Data processing involves reduction, presentation, and drawing conclusions or verification. To ensure the credibility of the results, data triangulation is used as a method of validity testing. Quantitative data are analyzed using descriptive statistical techniques and presented in narrative form to complement the qualitative findings. The research results reveal that the integration of Islamic values into academic supervision at the school is reflected in four key aspects: ihsan (benevolence), sincerity, exemplary behavior, and renewal. The promotion of these values by the school principal is perceived as strong, with average scores of 3.59, 3.63, 3.54, and 3.45, respectively. These values aim to foster trust, discipline, responsibility, and innovation among teachers, as well as enhance their well-being and work motivation. Interview findings further corroborate the observation data, indicating that Islamic values are consistently applied through various programs, such as regular study sessions, the Baitul Arqam program, and the creation of a respectful and supportive school environment. Overall, this research demonstrates that the integration of Islamic values in academic supervision has effectively supported the improvement of teacher performance and contributed to the advancement of educational quality at the institution. Abstrak: Penelitian ini bertujuan untuk menganalisis penerapan nilai-nilai Islam dalam pelaksanaan supervisi akademik di salah satu sekolah Muhammadiyah di Gowa. Metode penelitian yang digunakan adalah kombinasi (mixed methods). Penelitian ini difokuskan untuk mengetahui penerapan nilai-nilai Islam dan dampaknya terhadap kinerja guru. Instrumen penelitian yang digunakan berupa lembar observasi dan wawancara. Data primer dikumpulkan melalui observasi, wawancara, dan dokumentasi, sementara data sekunder diperoleh dari dokumen, buku, dan referensi relevan lainnya. Instrumen penelitian terdiri dari panduan observasi, panduan wawancara, dan pengumpulan dokumentasi. Pengolahan dan analisis data dilakukan melalui proses pengurangan data, penyajian data, serta penarikan kesimpulan/verifikasi, dengan pengujian validitas data menggunakan triangulasi data untuk meningkatkan kredibilitas hasil penelitian. Data kuantitatif dianalisis dengan teknik statistik deskriptif dan disajikan dalam bentuk naratif untuk memperkaya data kualitatif. Hasil penelitian menunjukkan bahwa integrasi nilai-nilai Islam dalam pelaksanaan supervisi akademik di salah satu sekolah di Gowa mencakup empat aspek utama: nilai ihsan, keikhlasan, keteladanan, dan tajdid. Penanaman nilai-nilai tersebut oleh kepala sekolah dalam supervisi pendidikan tergolong tinggi, dengan rata-rata nilai 3,59 untuk ihsan, 3,63 untuk keikhlasan, 3,54 untuk keteladanan, dan 3,45 untuk tajdid. Implementasi nilai-nilai ini melibatkan pembinaan amanah, disiplin, tanggung jawab, dan inovasi di kalangan guru, serta upaya untuk meningkatkan kesejahteraan dan motivasi kerja. Hasil wawancara memperkuat temuan dari observasi dan menunjukkan bahwa nilai-nilai Islam diterapkan secara konsisten melalui pengajian rutin, program Baitul Arqam, dan penciptaan lingkungan sekolah yang saling menghormati dan mendukung. Penelitian ini menunjukkan bahwa pelaksanaan supervisi akademik di salah satu sekolah Muhammadiyah di Gowa berhasil mengintegrasikan nilai-nilai Islam secara efektif, mendukung peningkatan kinerja guru, dan memberikan kontribusi terhadap kemajuan pendidikan di sekolah tersebut.